Efektivitas Podcast Edukatif sebagai Media Inovasi Pembelajaran Bahasa Indonesia di Era Digital: The Effectiveness of Educational Podcasts as an Innovative Medium for Indonesian Language Learning in the Digital Era - Melia Mardi; Desmimi Eka Putri; Yasmanelly Yasmanelly; Syofiani Syofiani (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
The digital era has brought fundamental changes to education, shifting the learning paradigm toward more intensive use of technology. The current generation, known as digital natives, has high expectations for the use of technology in the learning process. This requires educators to provide learning media that are innovative, interactive, and relevant to current developments. In Indonesian language learning, strategies are needed that can utilize technology while maintaining the nation's cultural and linguistic values. One medium with great potential is educational podcasts. This research used a qualitative method with a literature study approach. Data were collected through a review of various relevant literature sources, such as scientific journals and articles, to obtain a theoretical foundation. Data analysis was carried out in three stages: orientation to understand the topic in general, reduction to filter important information, and selection to select the most relevant data according to the research focus. The results of the study indicate that educational podcasts are effective as a medium for Indonesian language learning in the digital era. Podcasts provide easy access, improve listening skills, and stimulate student creativity. Their success is greatly influenced by integration with the curriculum, content development tailored to student needs, technological infrastructure support, and teacher training in managing this media. Despite challenges such as differences in student learning styles and varying content quality, solutions can be found through the use of multimedia, curated materials, and teacher competency development. Podcasts have significant potential to strengthen Indonesian language learning while preserving the richness of Indonesia's language and culture in the digital age.